Pendidikan Anak Perspektif Pendidikan Islam terhadap Fenomena Bullying di Lingkungan Sekolah - Nahuda Nahuda; Andriyani Andriyani; Mugiyono Mugiyono (SAP (Susunan Artikel Pendidikan), 2023)
Every child has the right to receive education and teaching from parents or other educational institution. Education is given with the expectation that children grow and develop properly, so that they become qualified children physically and spiritually, pious children. In the perspective of Islamic education, children are a mandate that must be maintained and their potential must be developed. The Covid 19 pandemic has changed the pattern of children's learning and social behavior which tends to experience a decline, from the behavioral aspect many negative things occur in the school environment. Bullying must be transformed into a children's habit of doing good to their friends. Love and compassion must be exemplified to minimize bullying that often occurs in the school environment. This study used a qualitative approach with a case study model of the phenomenon of bullying by children at school. This research aims to remind the importance of children and their education as a mandate, so the potential in children must be directed towards positive things so that in the future they can contribute to the nation state and religion.